Collective action within the household: Insights from natural resource management - Doss, Cheryl; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2014)
Households face many collective action situations, with members working together to produce livelihoods and allocate goods. But neither unitary nor bargaining models of the household provide frameworks to analyze the conditions under which households work collectively and when they fail to do so. Drawing on the Institutional Analysis and Development Framework based in the natural resource management literature, this paper explores the factors that encourage and inhibit collective action and provides insights into how to understand collective action problems within the household as dynamic, multi-actor situations with outcomes that can be evaluated by multiple criteria, not just efficiency. Comparison with the household literature also points to areas to strengthen the resource management literature through greater emphasis on human capital issues, including gender, health, and education.